The effectiveness of Gimkit in enhancing student’s reading skill - sugiyati; Syafryadin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This This study investigates the effectiveness of Gimkit, a game-based learning tool, in improving the reading skills of ninth-grade students at SMP Negeri Karya Sakti. The main objective of this research is to explore how using Gimkit, an interactive learning tool, can enhance students' reading skill. The research used a quantitative experimental design with two groups: one experimental class used Gimkit during reading lessons, while the control class followed traditional textbook-based instruction. Both groups took a pre-test before the lessons and a post-test after the lessons to measure improvement. The tests assessed vocabulary, comprehension, and reading fluency. The results showed a significant improvement in the experimental group’s scores, with an average increase of 16.80 points. A paired sample t-test confirmed the improvement was statistically significant (t = -10.602, p < .001). These findings suggest that Gimkit helps enhance reading skills by making learning more interactive and engaging. Features like instant feedback, rewards, and customisable quizzes also increased students’ motivation. It is recommended that educators integrate interactive digital tools like Gimkit into their teaching strategies to boost student participation and reading performance. Future research may explore the long-term impact of using such platforms and their application across different subjects and grade levels.